Penggunaan Asam Lemak Omega 3, Omega 6 dan Kolesterol Sintetis terhadap Kadar Hormon Testosteron dan Penampilan Reproduksi Puyuh Jantan (Coturnix coturnix japonica) - Fitriyah, Abyadul (Universitas Airlangga, 2008)
The purpose of this research is to know the effects of the using Omega 3, Omega 6 Fatty Acid and Cholesterol synthetic on Hormone Testosterone Level, voice frequency and male quails reproduction organ. The research used 175 male quails which were divided in to 7 treatment groups; R0 (control), R1 (0.163 mg eicosapentaenoic acid), R2 (0.326 mg eicosapentaenoic acid), R3 (0.163 mg 5,8,11,14 eicosatetraenoic acid), R4 (0.326 mg 5,8,11,14 eicosatetraenoic acid), R5 (20 mg cholesterol NF), R6 (40 mg cholesterol NF). Cholesterol and fatty acid treatment were given by oral for 5 day in succession for each treatment groups. Data was analyzed with one way analyse, and then continued with orthogonal contrast test and morpometri test. The out put of the research; the using of omega 3, omega 6 fatty acid with double dose (0.326 mg) showed the best respond, which were the increase of the testis weight, height, diameter and volume. The out put variance to the voice quality showed that treatments gave not significant effects the jumlah suku kotek (JSK), gave the significant effects (p<0.01) to the durasi kotek awal (DKA), gave tile significant effects (p<0.05) to the durasi kotek akhir (DKK) and gave not significant effects to the durasi kotek tengah (DKT). Base on orthogonal contrast test on DKA, R2, R3 and R6 significant (p<0.05) were heigher if thouse were compare with other treatment. It was also happen on DKK, the highest number was showed by double dose omega fatty acid and cholesterol (R4 and that R2 and R6). The highest hormone testosterone level was showed by R2 treatment. The conclution is that the using of 0.326 mg omega 3 and omega 6 fatty add effected the improvement of reproduction organ, voice quality and male quails blood plasma hormone testosterone level.